Molecular and bioinformatic analysis of the Persea americana (Mill.) NPR1-dependent defence signalling pathway in response to Phytophthora cinnamomi infection - Van den Berg, Noelani (University of Pretoria, 2024)
Thesis (PhD (Genetics))--University of Pretoria, 2019.